Structure and Characterization of Sulfated Chitosan Superplasticizer. Issue 6 (28th February 2013) - Lv, Shenghua; Cao, Qiang; Zhou, Qingfang; Lai, Shuili; Gao, Futang; Viehland, D.
<x xml:space="preserve">Abstract</x> A new sulfated chitosan superplasticizer (SCS) was synthesized by sulfation chitosan. The chemical structure and molecular weight of SCS were characterized by FTIR and gel permeation chromatography (GPC). The application performances of SCS in cement paste and concrete were investigated in the views of fluidity, slump, setting time, porosity as well as compressive strength. The results indicated that the SCS has better applied performance compared with polycarboxylate superplasticizer (PCs). A notable feature is that SCS has better maintenance for cement paste fluidity and concrete slump. The action mechanism behind this behavior was further revealed by zeta‐potential and adsorption amount. Meanwhile, SCS comes from renewable source and has biodegradability. This research work provides not only a new superplasticizer but also a method for preparing superplasticizer from the renewable biopolymer.